Strategic business movements? The migration of online romance fraudsters from Nigeria to Ghana - Suleman Lazarus; Mark Button; Kaina Habila Garba; Adebayo Benedict Soares; Mariata Hughes (Journal of Economic Criminology)
This study used an emic approach to examine the dynamics of online romance fraud, focusing on the migration of offenders from Nigeria to Ghana. We collected data through qualitative methods, such as semi-structured interviews and focus group discussions. Ghanaian police officers and Nigerian law enforcement officers were consulted for their perspectives. Thematic analysis revealed key findings, including the migration patterns of Nigerian offenders to Ghana and the institutionalisation of scamming enterprises. These findings shed light on the transnational and structural factors driving online romance fraud in West Africa, highlighting both its global reach and the local mechanisms sustaining these criminal networks. This research contributes to a deeper understanding of regional and international cybercrime dynamics, offering valuable insights to inform policy and law enforcement strategies.